Cumulative Incidence of Revision for a Balanced Knee System at a Mean 8-Year Follow-Up: A Retrospective Review of 500 Consecutive Total Knee Arthroplasties - Michael H. Bourne; Tony L. Miller; E. Marc Mariani (Advances in Orthopedics)
Purpose. The primary purpose of this study was to evaluate mid-term survival of a Balanced Knee System in the first 500 total knee arthroplasty (TKA) cases using a fully cemented, posterior stabilized TKA at a high-volume private practice. Patients and Methods. In this IRB approved retrospective cohort study, data were extracted from a surgical registry at a high-volume orthopaedic practice for the first 500 total knee arthroplasty (TKA) cases performed using the Balanced Knee® System (BKS, Ortho Development®, Draper, Utah, USA). Procedures were performed between June 2000 and September 2003 by one of two orthopaedic surgeons. Follow-up was performed at 6 weeks, 6 months, 1 year, 5 years, and 10 years. 48 patients (9.6%) were considered lost to follow-up. A competing risk analysis was performed to evaluate the cumulative incidence of revision while accounting for the competing risk of death. In the model, failure was defined as revision of any BKS component. Those who failed prior to two years remained in the analysis. Results. The mean age of the population was 69 years (range: 40–94) and 73% were female. The cumulative incidence of revision of any component was approximately 1% at a mean 8-year follow-up (range: 0.11–14.1 years) when accounting for the competing risk of death. When considering all those lost to follow-up as failures, the cumulative incidence of failure at 8 years was approximately 10%. Conclusion. Based on the results of the current study, a posterior stabilized primary TKA, implanted using a flexion and extension gap balancing technique, had excellent survivorship and outcomes at a mean 8-year follow-up.